Thailand Economic Monitor, July 2021 : The Road to Recovery - World Bank (World Bank, Washington, DC, 2021)
Successive waves of COVID-19 disrupted the Thai economy in the first half of 2021, but their impact was mitigated by recovering global demand and substantial fiscal support. After a second wave of COVID-19 infections began in late 2020, the government strengthened public health and social distancing measures to contain the renewed spread of the virus. The shock of the second wave caused the economy to contract by -2.6 percent, year-on-year (yoy), in Q1 2021, following a 6.1 percent drop in GDP in 2020 which was one of the steepest contractions among Association of Southeast Asian Nations (ASEAN) member states. While private investment and manufacturing production recovered to near pre-COVID levels in the first quarter of 2021, weakness in the services and agricultural sector persisted. A third wave of infections that emerged in April 2021 has proven especially severe, and the number of cases surged to over 3,000 per day in May-June 2021. Strict containment measures have reduced mobility and negatively affected consumption and business sentiment. Activity in the tourism sector has remained negligible, and the outlook is clouded by the ongoing impact of COVID-19 across the region, the emergence of new variants, and slow progress on vaccination. However, rebounding goods exports have provided substantial support to the Thai economy, driven by recovering global demand for automotive parts, electronics, machinery, and agricultural products. Cash transfers, public health initiatives, economic recovery programs and other forms of fiscal support have helped shore up private demand while supporting consumption among vulnerable households and attenuating the impact of the crisis on poverty. Going forward, government will need to invest in strengthening the social protection system. Prior to the pandemic social assistance benefits were not very generous and often inadequate to protect the poor. The largest social assistance programs were categorically targeted, and only recently is poverty targeting becoming more prominent. In the years to come it should be a priority to ensure that vulnerable beneficiaries receive adequate support and given the limited fiscal space would also require significant investments in effective targeting. The crisis also further underscores the need to ensure that the social protection system covers the large informal sector in Thailand at all times, not only during crises.